2006
DOI: 10.1051/0004-6361:20065052
|View full text |Cite
|
Sign up to set email alerts
|

The Galactic WN stars

Abstract: Context. Very massive stars pass through the Wolf-Rayet (WR) stage before they finally explode. Details of their evolution have not yet been safely established, and their physics are not well understood. Their spectral analysis requires adequate model atmospheres, which have been developed step by step during the past decades and account in their recent version for line blanketing by the millions of lines from iron and iron-group elements. However, only very few WN stars have been re-analyzed by means of line-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
580
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 352 publications
(632 citation statements)
references
References 61 publications
49
580
3
Order By: Relevance
“…1 presents the WR mass-loss rates given by NL and TSK at solar metallicity, compared to the empirical values of Galactic hydrogen-free WR stars 1 . Note that the Potsdam group inferred mass-loss rates with clumping factors of D = 4 for Galactic WNE stars and with D = 10 for WC stars, respectively (Hamann et al 2006;Sander et al 2012). Given that both NL and TSK prescriptions are based on the data compatible with D = 10 rather than with D = 4, here we corrected the WNE mass-loss rates of the Potsdam group by a factor of (4/10) 0.5 for this comparison.…”
Section: Mass Loss Rates Of Wr Starsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 presents the WR mass-loss rates given by NL and TSK at solar metallicity, compared to the empirical values of Galactic hydrogen-free WR stars 1 . Note that the Potsdam group inferred mass-loss rates with clumping factors of D = 4 for Galactic WNE stars and with D = 10 for WC stars, respectively (Hamann et al 2006;Sander et al 2012). Given that both NL and TSK prescriptions are based on the data compatible with D = 10 rather than with D = 4, here we corrected the WNE mass-loss rates of the Potsdam group by a factor of (4/10) 0.5 for this comparison.…”
Section: Mass Loss Rates Of Wr Starsmentioning
confidence: 99%
“…However, consideration of wind clumping (e.g., Moffat & Robert 1994;Lépine & Moffat 1999) in later empirical estimates of WR mass-loss rates resulted in much lower values (e.g., Hamann & Koesterke 1998;Hamann et al 2006;Crowther 2007;Sander et al 2012). For example, currently the most popular prescription by Nugis & Lamers (2000, hereafter, NL) gives WR massloss rates almost 10 times lower than those used in the above-quoted theoretical studies.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hamann et al 2006;Crowther et al 2010;Hainich et al 2014;Bestenlehner et al 2014). The HRD positions of these objects suggest that they are very massive stars (VMS) with initial masses in excess of ∼100 M , and reaching up to 300 M (cf.…”
Section: Wr Populations In the Galaxy And Lmcmentioning
confidence: 98%
“…Comprehensive studies of the local population of WR stars of the nitrogen sequence (WN stars) have been performed for the Galaxy by Hamann et al (2006) The dividing luminosity at roughly 10 5.9 L suggests that the classical WN stars are core He-burning objects in a post-red supergiant (post-RSG) phase. This picture is further supported by the work of Sander et al (2012), who found that the WR stars of the carbon sequence (WC stars), which are showing the products of He-burning at their surface, form a natural succession of the sequence of classical WN stars in the HR diagram (HRD).…”
Section: Wr Populations In the Galaxy And Lmcmentioning
confidence: 99%